Case Report: Stevens-Johnson Syndrome and Hepatotoxicity Induced by Osimertinib Sequential to Pembrolizumab in a Patient With EGFR-Mutated Lung Adenocarcinoma - Gianni, Caterina; Bronte, Giuseppe; Delmonte, Angelo; Burgio, Marco Angelo; Andrikou, Kalliopi; Monti, Manlio; Menna, Cecilia; Frassineti, Giovanni Luca; Crinò, Lucio (Frontiers in Pharmacology, 2021)
Background: Lung cancer is a complex disease with many subtypes. However, histochemical characteristics, and genetic mutation determinations are contributing to better define therapeutic targets and new drugs. Although this guarantees patients the possibility of obtaining tailored treatment, it makes it more difficult for clinicians patient management more difficult for clinicians who have to define the most suitable therapeutic strategy and to deal with new treatment-related adverse events (TRAEs). It has been seen that the administration of a tyrosine kinase inhibitor (TKI) sequential to an immune checkpoint inhibitor (ICI) can lead to a higher rate of severe and life-threatening TRAEs. We report the case of a patient with advanced non-small cell lung cancer (NSCLC) who experienced severe hepatotoxicity and Stevens-Johnson syndrome (SJS) induced by osimertinib sequential to pembrolizumab. Case presentation: A 54-year-old woman with advanced NSCLC received one cycle of chemotherapy plus pembrolizumab after diagnosis. Ten days later she began osimertinib 80 mg daily because epidermal growth factor receptor (EGFR) analysis had revealed an exon 19 deletion. On day 23 of osimertinib the patient experienced an episode of grade (G) 3 hepatotoxicity resolved by discontinuing osimertinib and corticosteroid therapy. The patient restarted osimertinib 80 mg daily after the remission of symptoms but was hospitalized 14 days later following a second episode of severe G3 hepatotoxicity and the onset of SJS, successfully treated with high-dose corticosteroids. Despite the short exposure to osimertinib, the patient obtained a good pathological response. Conclusion: It is important to alert clinicians to carefully evaluate the sequential therapeutic strategy in patients with NSCLC who are candidates for TKI- or ICI-based treatment. Our experience suggests that the use of tyrosine kinase inhibitors (TKIs) as front-line treatment is a more reasonable and safe option for EGFR-mutated lung adenocarcinoma, with ICIs considered as a possible further treatment in sequential approaches.